Implikasi Yuridis Peraturan pemerintah tentang Pungutan Otoritas Jasa Keuangan Terhadap Notaris Pemegang Surat Tanda Terdaftar yang tidak pernah Berkegiatan di Pasar Modal - Puspitasari, Ratna Ayu; Koeswahyono, Imam; Soekesi, Titik Soeryati (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2019)
This paper aims to describe the authority of the Financial Services Authority (OJK) in conducting supervision and regulation of the financial services sector, and the juridical implications of Government Regulation Number 11 of 2014 concerning OJK Levy for capital market notaries registered with Registered Letters (STTD) who are not active in the capital market. The research method used in this paper is a normative juridical. The results of the study indicate that the OJK has the authority to levy notaries. Legal implications arising from Government Regulation Number 11 of 2014 concerning Financial Services Authority Levies for notaries who have STTD but do not engage in capital market activities becomes the state’s receivables. Payments will be made by the state receivable committee, with a forced letter that has the same legal force as the Grosse deed.